Learning Leadership: Leading Growth in a Transactional System - Wood, Kevin (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2023)
Learning Leadership is a framework that addresses the complex actions and decisions made by principals. Harris and Jones (2021) declared the need to deepen an understanding of how educational leaders support conditions inherent to learning organizations. This study sought to better understand how principals learn and support growth as a strategy for leading. Findings are presented from seven Alberta, Canada high schools where principals were asked to reflect on learning leadership. Open interviews generated data about learning as both an outcome and a method of leading.Interview data was analyzed through van Manen’s (2016) three step interpretive scheme and yielded themes describing how high school principals mediated in-school realities with external expectations. Study findings indicate that principals who lead for learning and achievement were able to identify growth-minded solutions characterized by ethical and wise approaches.